Os italianos da Operação Mato Grosso (OMG) em Poxoréu : uma construção artístico-cultural - Santos, Djalma Alves dos (2019)
The aim of this dissertation is to analyse the acts of the Italian volunteers of “Operazione Mato Grosso” or Operation Mato Grosso (OMG), in Poxorèu, MATO GROSSO, beginning in 1967, contributing in this way to scientific production about this theme. From a qualitative research, studying this case, we can analyse the meaning of this movement, how it has evolved, all dynamics, cultural and social impact on the activities who benefited from it. About that, the emphasis is placed on the cultural issue, this include the formation of artistic and religion schools in all its unit, called Don Bosco’s houses. The artistic activities are the main aspects analyzed in this study, their concepts have been deal with various forms of learning, aesthetic experimentation and art production conducted by the Italians in the training and production workshops. For the construction of this dissertation, the methodology includes the bibliographical studies and related documentation, through different bibliographical references about the beginning of OMG, and the open interviews, by means of which are obtained testimony of volunteers who work in this context since 1967. With regard to the techniques and the influence of Italian style taught in these laboratories, the quest based on the bibliography research, with bibliographical reference and images, beyond that the qualitative material and visual analysis, establishing a connection with results of arts and crafts laboratories. Among the various arts teaching, from the Italian point of view, this dissertation presents in particular the Art of Inlay. Considered an ancient art, has arrived in Poxorèu thanks to the Italian artist, Luigi Galimberti, within a dynamic “mestiere d’arte” heritage, this term is considered an Italian cultural concept. Finally, we have notice that during the time the actions of the OMG took into account, above all things, the meaning of Art and culture in the Eurocentric perspective. Especially the Italian one, as well as the conceptions of movement, voluntary action, which in the considerations of the studies of Nicolas Bruce was based on the gestures of his idealizer, Ugo De Censi, as poetry of charity.